فاعلية استراتيجية المشاريع الإلكترونية في تنمية بعض مهارات تدريس الرياضيات لدى الطالبات المعلمات تخصص صفوف أولية واتجاهاتهن نحوها - السيد، صباح عبدالله عبدالعظيم (جامعة القاهرة - كلية الدراسات العليا للتربية, 2020)
هدفت الدراسة تعرف استراتيجية المشاريع الإلكترونية وأثرها على مهارات تدريس الرياضيات والاتجاه نحوها لدى الطالبات المعلمات تخصص معلم صفوف أولية، وقد تم صياغة بعض موضوعات مقرر طرق تدريس الرياضيات للطالبات تخصص معلم صفوف أولية باستراتيجية المشاريع الإلكترونية، وتم إعداد بطاقة ملاحظة لقياس مهاراتهن في تدريس الرياضيات، ومقياس للاتجاهات نحو استراتيجية المشاريع الإلكترونية. وتم تطبيق الدراسة على 35 طالبة من طالبات المستوى السابع تخصص صفوف أولية، وكانت نتائج الدراسة كالتالي: (1) وجد فرق ذو دلالة إحصائية بين متوسطي درجات الطالبات في القياسين البعدي، والقبلي لبطاقة الملاحظة لصالح القياس البعدي. (2) وجد فرق ذو دلالة إحصائية بين متوسطي درجات الطالبات في القياسين البعدي، والقبلي لمقياس الاتجاهات نحو الاستراتيجية لصالح القياس البعدي. (3) كان معامل بلاك المعدل أكبر من 1.2 في كل من بطاقة الملاحظة ومقياس الاتجاهات نحو الاستراتيجية المشاريع الإلكترونية، وهذا يؤكد فاعلية استراتيجية المشاريع الإلكترونية على مهارات التدريس والاتجاهات نحوها لدى الطالبات المعلمات تخصص صفوف أولية.
This research purposes to find the impact of the electronic projects strategy to develop some mathematical teaching skills and the attitudes towards it among female primary teacher students. To accomplish this, some topics of teaching mathematics course of the female primary teacher was formulated as stated by the electronic projects" strategy. Moreover, two tools were developed: An observation card, and an attitude toward the strategy scale. A sample of 35 female primary teacher students studied some topics of teaching mathematics course with the electronic projects' strategy. Results of the research displayed that: (1) There was significant development in mathematical teaching skills between pre- and post-measurement in the observation card in favor of post-measurement.(2) There was significant development in the attitudes toward e-projects' strategy between pre- and post-measurement in the attitudes scale in favor of post-measurement. (3) the black modified gain ratio was high in the observation card and the attitudes scale and this exposed the impact of Using the e- projects' strategy to Develop some mathematical teaching skills and the attitude towards the strategy among female primary teacher students.
Keywords: الاستراتيجيات التعليمية -- التعليم الإلكتروني -- المشاريع الإلكترونية -- المهارات التدريسية -- تدريس الرياضيات